2019
DOI: 10.1002/prot.25791
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico studies on membrane interactions of diverse Capsicum annuum flower γ‐thionin peptides

Abstract: Thionins are small, cysteine‐rich peptides that play an important role in plant defense, primarily through their interactions with membranes. Eight novel γ‐thionin peptides (CanThio1‐8) were isolated from the flower of Capsicum annuum. Sequence analysis revealed that the peptides cluster into three groups. A representative peptide from each group (CanThio1, 2, and 3) was used for experimental characterization. Interestingly, peptides were found to possess some cytotoxic activity against normal human embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The α-core structure is a loop comprising the first β chain and the helix, while the γ-core structure is an area comprising the hairpin loop and it connects the second and third β-chains . [50,69] In one study, it was found that cowpea's plant defense protein VuD1 binds to the active site of amylase mainly through an N-terminal structure. Lys1 is obtained from VuD1, while Asp240 is obtained from Z.subfasciatus α-amylase (ZSA).…”
Section: Study Of the Structure And Mechanism Of Proteinaceous α-Amylase Inhibitorsmentioning
confidence: 99%
“…The α-core structure is a loop comprising the first β chain and the helix, while the γ-core structure is an area comprising the hairpin loop and it connects the second and third β-chains . [50,69] In one study, it was found that cowpea's plant defense protein VuD1 binds to the active site of amylase mainly through an N-terminal structure. Lys1 is obtained from VuD1, while Asp240 is obtained from Z.subfasciatus α-amylase (ZSA).…”
Section: Study Of the Structure And Mechanism Of Proteinaceous α-Amylase Inhibitorsmentioning
confidence: 99%
“…Plant γ -thionins can occur in all tissues including the female gametophyte, flowers, pollen, shoots, cotyledons, leaves, roots, bark, the endosperm of immature kernels and fruits. Their functional roles depend on the specific interactions with the plasma membrane (reviewed by Gomes, 2009, 2011;De Coninck and De Smet, 2016;Nikte et al, 2020). Several plant γ -thionins have been shown to induce the accumulation of intracellular ROS and to initiate PCD that are part of regulatory cascades leading to the protection or tolerance against pathogens (Hegedüs and Marx, 2013).…”
Section: Other Cysteine-rich and The Small Post-translationally Modified Peptidesmentioning
confidence: 99%
“…40,41 Gold-palladium core-shell nanobones (Pd@Au NBs) with larger specific surface area than gold nanorods (AuNRs) can be used as a carrier for immobilizing DNA strands and binding numerous Thi by Au-N bonds and Pd-N bonds. [42][43][44] Therefore, Thi-labeled Pd@Au NBs were synthesized as signal probes to reflect the signal changes generated by the recognition process.…”
Section: Introductionmentioning
confidence: 99%